ASEAN enlargement impacts and implications - Mya Than; Gates, Carolyn (Institute of Southeast Asian Studies, 2001)
Since 1995, the ASEAN grouping has been extended to include Vietnam, Laos, Myanmar and Cambodia. ASEAN's focus has changed from political and military security to economic cooperation and development. This work explores economic and political issues confronting the enlarged ASEAN-10.